Crustal Structure of Etna Volcano (Italy) From P‐Wave Anisotropic Tomography - R. Lo Bue; F. Rappisi; M. Firetto Carlino; E. Giampiccolo; O. Cocina; B. P. Vanderbeek; M. Faccenda (Geophysical Research Letters)
Abstract Several seismic tomographic studies have been carried out to outline the intricate interplay between tectonics and magma uprising at Etna volcano. Most of these studies assume a seismically isotropic crust. Here we employ a novel methodology that accounts for the anisotropic structure of the crust. Anisotropy patterns are consistent with the Etna structural trends, unveiling the depth extent of fault segments. A high‐velocity volume, deepening toward the northwest, identifies the subducting foreland units that appear to confine a low‐velocity anomaly, interpreted as the expression of magmatic fluids within the crust. A discontinuity, likely tectonic in origin, affects the subducting units and allows magma transfer from depth to the surface. This structural configuration may explain the presence of such a very active basaltic strato‐volcano within an atypical collisional geodynamic context.